DIGITALISASI BUDAYA BALI: MEDIA AR SEBAGAI BENTUK REVITALISASI AKSARA BALI - NURHUDA, TRIFALAH; PURNAMI, IDA AYU PUTU; WISNU, I WAYAN GEDE; JONIARTA, I MADE (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
Balinese script is one of the cultural heritages of the Balinese people that has become increasingly marginalized in today's era of globalization. This study aims to design and evaluate Augmented Reality (AR)-based learning media as a form of cultural revitalization for Bali. The research was conducted using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation) to create interactive learning media tailored to the needs of students and teachers. The results of the study indicate that the Balinese Script AR media significantly enhances students' interest and understanding of Balinese script, receiving an average rating of "excellent" (96.5% by subject matter experts and 88.26% by students). Teachers also provided highly positive feedback, with an average score of 97.5%, as the media effectively supports the learning process. In addition to serving as an interactive educational tool, this media contributes to the preservation of local culture by connecting younger generations to the heritage of their ancestors. This research concludes that AR-based learning media holds great potential for supporting both the learning process and the revitalization of Balinese script in the digital era. ABSTRAKAksara Bali merupakan salah satu warisan budaya Masyarakat Bali yang seiring dengan perkembangan semakin terpinggirkan di era globalisasi saat ini. Penelitian ini bertujuan untuk merancang dan mengevaluasi media pembelajaran berbasis Augmented Reality (AR) sebagai bentuk revitalisasi budaya Bali. Penelitian dilakukan dengan menerapkan model pengembangan ADDIE (Analyze, Design, Development, Implementation, Evaluation) untuk menciptakan media pembelajaran interaktif yang sesuai dengan kebutuhan siswa dan guru. Hasil penelitian menunjukkan bahwa media AR Aksara Bali mampu meningkatkan minat dan pemahaman siswa terhadap aksara Bali dengan penilaian rata-rata sangat baik (96,5% oleh ahli materi dan 88,26% oleh siswa). Guru juga memberikan penilaian yang sangat positif, dengan skor rata-rata 97,5%, karena media ini mendukung proses pembelajaran secara efektif. Selain berfungsi sebagai alat edukasi interaktif, media ini juga berkontribusi dalam pelestarian budaya lokal dengan menghubungkan generasi muda dan warisan budaya leluhur mereka. Penelitian ini menyimpulkan bahwa media pembelajaran berbasis AR memiliki potensi besar dalam mendukung pembelajaran dan revitalisasi aksara Bali di era digital.